Visible Domain Photocatalysis Performance of Ti-Si Thermal-Sprayed Coatings - Uncu, Ionut; Roata, Ionut Claudiu; Croitoru, Catalin; Machedon-Pisu, Teodor (MDPI- Sustainability, 2022)
Cost and performance-effective materials used in advanced oxidation processes such as photocatalysis have obtained widespread attention in recent years. In this study, thermal spraying was used as a one-step method to obtain thick visible-light-active photocatalyst coatings on two types of substrates, namely, plain carbon steel and copper. A mixed metallic titanium–silicon powder bearing 10% wt. Si was used as feedstock. The optical bandgaps of the coatings were close to 1.000 eV, allowing good photodecoloration efficiencies (>89%) and mineralization efficiencies (>67%) for methylene blue dye from aqueous solutions under visible light irradiation. The photodegradation process could be successfully modelled by the Langmuir–Hinshelwood pseudo-first-order kinetic model, with reaction rate constants k between 0.16 and 1.06 h−1.
Keywords: photocatalysis; thermal spraying; advanced oxidation processes; wastewater treatment